Avaliação nutricional e laboratorial de dois programas para perda de peso em indivíduos obesos: dieta tradicional X dieta Dukan - Sakae, Patricia Naomi [UNIFESP] (2017)
Introduction: Diets with carbohydrate restriction has been widely used by the population aiming at weight loss. Among them, Dukan diet, with high protein content and carbohydrate and fat restriction has been widely used for weight loss. Objective: To compare nutritional, laboratory and endothelial function parameters in obese subjects submitted to the Dukan diet with those submitted to traditional low calorie diet. Methods: Subjects with obesity classes I or II, from both genders, aging 19 to 65 years, were included in the study and allocated into two groups: Traditional low-calorie diet (n = 17) and Dukan Diet (n = 17). The traditional diet group received counselling according to the recommendations of the Guia Alimentar para a População Brasileira (Ministério da Saúde, 2006) and the Dukan diet group followed the high-protein diet with carbohydrate restriction. Clinical, nutritional, and laboratory evaluations were performed at baseline, 3, 6 and 12 months. The endothelial function was assessed by flow-mediated dilatation of the brachial artery, at same times. Statistical analysis was performed by Student t test for comparison between groups and repeated measure analysis of variance (ANOVA) followed by Tukey test for comparison the values in the times in each group. Results: In the Dukan diet group, there was an imbalance in the food intake of macro and micronutrients with reductions in calories, proteins, carbohydrates, lipids, fibers, saturated, polyunsaturated and monounsaturated fats and magnesium. In the traditional diet group there was reduction only in calories and vitamin B12. After 12 months, it was verified that the Dukan diet was more effective (p<0.05) than traditional diet for the following anthropometric parameters: weight loss (-10.6 kg and -2.9 kg), body mass index (-3.7 kg/m2 and -1.1 kg/m2 ), waist circumference abdominal (-11.2 cm and -2.1 cm), body composition with loss in fat (-5.7 kg and -2.0 kg), lean mass (-4.8 kg and -0.8 kg) and basal metabolic rate (-152 cal and -28 cal). Laboratory changes observed in the Dukan diet group include improvement (p<0.05 vs. baseline) in triglyceride levels (172.40 ± 62.36 mg/dL to 111.90 ± 43.22 mg/dL) and insulin resistance, based on HOMA-IR index (4.98 ± 3.03 to 3.26 ± 2.03, p<0.05 vs. baseline). The glomerular filtration rate decreased in this group (132.50 ± 31.13 mL/min to 113.80 ± 24.25 mL/min, p<0.05 vs. baseline) after 3 months, and no significant change was observed in the endothelial function in any group. Conclusion: The Dukan Diet was more effective than traditional diet for weight loss in the 12-months follow-up in obese subjects. Some improvement on biochemical parameters was observed, without changes in endothelial function.